1999
DOI: 10.1046/j.1365-3083.1999.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Immunopotentiators on the Antiporin Immunoglobulin G Subclass: Distribution and Protective Immunity Against Murine Salmonellosis

Abstract: To improve the immune potential of porin (a pore‐forming protein of Salmonella sp.), different immunopotentiators such as Freund's complete adjuvant (FCA), lipopolysaccharide (LPS) and polyoxydonium (PO) were evaluated by studying the nature of the protective immune response induced against murine Salmonellosis. The nontoxic, synthetic heteropolymer polyoxydonium was as good as LPS at inducing antiporin immunoglobulin G (IgG) antibodies and protective immunity. Analysis of the antiporin IgG subclass pattern re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that salmonella porins induce the production of predominantly IgG1 after 30 days in BALB/c mice 42 . We have recently reported that human volunteers vaccinated with S .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies have demonstrated that salmonella porins induce the production of predominantly IgG1 after 30 days in BALB/c mice 42 . We have recently reported that human volunteers vaccinated with S .…”
Section: Introductionmentioning
confidence: 85%
“…This notable immunogenicity of porins to sustain bactericidal antibody memory response could be explained by either of the following non‐exclusive mechanisms. First, because salmonella porins are good immunogens 20,21 , 27,33 , 36–42 and porins from other pathogens have been identified as TLR2 agonists 29–31 . Thus, during the initial immune response, it is possible that salmonella porins might be simultaneously recognized by B‐cell receptors and innate receptors, such as TLRs, thereby inducing the differentiation of naive B cells into effector antibody‐secreting plasma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Water-soluble, non-toxic and synthetic polyelectrolytes were found to be efficient immunomodulators [88]. A more prominent increase in antibody responses was achieved by complexing an outer membrane protein of Salmonella, porin, with the heteropolymer, polyoxydonium [89]. Similarly, Salmonella O and H antigens complexed with polyelectrolytes have been shown to induce several-fold higher antibody responses against respective antigens [90].…”
Section: Polyelectrolytesmentioning
confidence: 99%